Analysis Of Character Development On Acting Class By Konstantin Stanislavsky - Oktav Berlianov (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2024)
This research explores of acting class that there were use as a tool to demonstrates a widening gap between verbal communication skills expectations of employers and the perceived abilities of higher education graduates. Recent studies have also suggested that the art of acting is an effective pedagogical tool for developing oral communication skills. This research using descriptive qualitative method with data collection techniques carried out by watching and documenting drama. The data validity technique used is source triangulation, while the data analysis technique uses interactive data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study showed that there were 15 element of character development consisting of Oral Communication Skills, Creative Problem Solving Abilities, Motivation and Commitment, Willingness to Work Cooperatively, The Ability to Work Independently, Promptness and Respect for Deadlines, Acceptance of Rules, Respect for Colleagues, Adaptability and Flexibility, Self-Discipline, Concentration, A Goal-Oriented Approach to Work, Dedication, A Willingness to Accept Responsibility, Self-Confidence. This study also found the relevance of acting class to character improvement. The results of this study can provide important meaning for the development of a person's character through acting class activity.